2018
DOI: 10.1021/acs.langmuir.8b03025
|View full text |Cite
|
Sign up to set email alerts
|

Probing Wettability Alteration of the Boron Nitride Surface through Rheometry

Abstract: While the surface of many ceramic particles is covered by positive and negative species, boron nitride displays no charge on the surface. Nevertheless, the interest in boron nitride is rising: Little materials combine electrical insulation and high thermal conductivity; both properties are required for many applications, for instance, in electronic devices and sensors. Hydroxyl (-OH) groups are usually created on the surface to increase the hydrophilicity of particles. In this work, we compare four treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…However, due to the very low amount of hydroxyl groups compared with the size of the h-BN sheets, the presence of those hydroxyl groups were not visible with FTIR. This is in accordance with the literature [33]. The TGA (Figures 3b and 4b) of BNO Cal/W also showed a weak weight loss in comparison to h-BN that confirmed the difficulty of assessing a high hydroxylation rate.…”
Section: Hydroxylation Of H-bn (Tga and Ftir)supporting
confidence: 91%
See 1 more Smart Citation
“…However, due to the very low amount of hydroxyl groups compared with the size of the h-BN sheets, the presence of those hydroxyl groups were not visible with FTIR. This is in accordance with the literature [33]. The TGA (Figures 3b and 4b) of BNO Cal/W also showed a weak weight loss in comparison to h-BN that confirmed the difficulty of assessing a high hydroxylation rate.…”
Section: Hydroxylation Of H-bn (Tga and Ftir)supporting
confidence: 91%
“…Wu et al [32] demonstrated the hydroxylation of h-BN by sonicating h-BN particles in a nitric acid solution. Korycki et al [33] compared four treatments to select the one that increased the hydrophilicity of h-BN platelets most significantly and therefore resulted in the highest concentration of the -OH groups grafted on sheet edges. As the results were proximate, the authors selected a thermal treatment that was more environmentally friendly than the use of strong acids or bases.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although this makes breakage of B−N bonds challenging, several chemical modification strategies have still been developed successfully. 7,8 In general, most of them rely on strong acids, 9 strong bases, 10,11 strong oxidants, 12 highenergy rays, 13,14 or other harsh experimental conditions. 15 For example, adding h-BN to HNO 3 (or a mixed solution of HNO 3 and H 2 SO 4 ) solution (∼65% w/w) and sonicating for 5−6 h can introduce hydroxyl groups on the surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the difference in electronegativity between B and N makes the covalent sp 2 bonds partially ionized, which makes B–N bonds stronger and harder to break . Although this makes breakage of B–N bonds challenging, several chemical modification strategies have still been developed successfully. , In general, most of them rely on strong acids, strong bases, , strong oxidants, high-energy rays, , or other harsh experimental conditions . For example, adding h-BN to HNO 3 (or a mixed solution of HNO 3 and H 2 SO 4 ) solution (∼65% w/w) and sonicating for 5–6 h can introduce hydroxyl groups on the surface. , In addition, after acid oxidation, H 2 O 2 can be used to further increase the hydroxyl content. , The strong alkali treatment generally involves adding h-BN to solutions such as 5 M NaOH or KOH and heating to reflux for a period of time; ,, this is one of the most widely used methods to introduce hydroxyl groups on the edges of h-BN in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite active endeavors, it is still challenging to realize different wettability on BNrelated materials. 22,[38][39][40][41][42] Also, there is a possibility that the asobtained wetting states could only sustain for a short time. 22 Compared with the previous efforts, our work demonstrated not only the effective fabrication of the BN aerogel with varied microstructures but the tuning of wetting behavior without involving any special treatment, which are widely employed in wettability modulation, such as irradiation, etching, or coating.…”
mentioning
confidence: 99%